Cooperating out of poverty the renaissance of the African cooperative movement - Develtere, Patrick; Pollet, Ignace; Wanyama, Fredrick (ILO, 2008)
Traces the historical path of cooperatives and trends since the 1990s. Gives examples from eleven countries in Africa of successful, genuine and economically viable cooperatives, and how they create economic opportunities and a basic level of social protection and security, and provide their members with voice and representation.